2015
DOI: 10.1111/jdi.12421
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐free mass and calf circumference as body composition indices to determine non‐exercise activity thermogenesis in patients with diabetes

Abstract: Aims/IntroductionTo investigate the clinical and anthropometrical parameters that are associated with non‐exercise activity thermogenesis that is composed of basal energy expenditure (BEE) and diet‐induced thermogenesis (DIT) in patients with diabetes.Materials and MethodsBody composition was assessed using bioelectrical impedance, and BEE and DIT were measured using indirect calorimetry in 40 Japanese patients with diabetes.Results BEE correlated positively with bodyweight, body mass index, fat mass, and fat‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Furthermore, an association of CC with insulin resistance and carotid atherosclerosis was reported [14]. Recently, we found that lean body mass and CC are associated with basal energy expenditure and partly with diet-induced thermogenesis in patients with diabetes [6]. Together with the present findings, we propose to measure CC to estimate lean body mass and the potential protection against obesity-associated insulin resistance and metabolic abnormalities during routine health examinations.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, an association of CC with insulin resistance and carotid atherosclerosis was reported [14]. Recently, we found that lean body mass and CC are associated with basal energy expenditure and partly with diet-induced thermogenesis in patients with diabetes [6]. Together with the present findings, we propose to measure CC to estimate lean body mass and the potential protection against obesity-associated insulin resistance and metabolic abnormalities during routine health examinations.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study reported that subjects with increasing CC had significantly higher basal energy expenditure and diet‐induced thermogenesis . Moreover, CC reflected fat free mass more than BMI or WC . Also, reduced thigh and calf circumferences were positively correlated with insulin resistance and carotid atherosclerosis .…”
Section: Discussionmentioning
confidence: 86%
“…The mechanism of sarcopenic obesity was not fully evaluated. A previous study reported that subjects with increasing CC had significantly higher basal energy expenditure and diet‐induced thermogenesis . Moreover, CC reflected fat free mass more than BMI or WC .…”
Section: Discussionmentioning
confidence: 88%
“…While no other studies have been found using the same tools as our investigation to measure body composition, a lot of research has been carried out on cardiovascular risk markers other than AS. It should also be noted that fat-free mass represents the weights of muscle, bone, and internal organs [41] and we found several examples of different research approaches relating to our analysis, but where FFMI was evaluated, like lean body mass, with measurements taken by means of bioimpedance, skinfolds, or a Dual-energy X-ray absorptiometry (DXA) scanner. In general, our data are in line with the results from a study of adolescents, in which lean mass (derived from skinfold and bioimpedance measurements) was one of the variables most strongly associated with cardiovascular risk parameters, such as systolic blood pressure, maximal oxygen uptake (VO 2 max), or triglycerides [42].…”
Section: Discussionmentioning
confidence: 99%